influencia de la densidad de corriente y dosis de hipoclorito de sodio sobre la resistencia a la corrosión del acero inoxidable aisi 304 protegido catódicamente con corriente impresa, expuesto en agua de mar natural contaminada con hipoclorito - Broncales Bazan, Wendy Jahaira (2019)
In this research, it was evaluated the influence of the current density and sodium hypochlorite dose on the corrosion resistance of AISI 304 stainless steel protected cathodically with impressed current, when was submerged in natural seawater contaminated with sodium hypochlorite. For data collection, rectangular specimen of AISI 304 stainless steel, with dimensions of 50x25x1 mm, were immersed in a solution of seawater with a sodium hypochlorite dose of 5, 10 and 15 mL/L, applying cathodic impressed current, for a period of 7 days with constant agitation. The corrosion resistance of these materials was determinated by pitting count according to ASTM G 46-94. Finally, it was established that AISI 304 stainless steel, immersed in natural sea water contaminated with sodium hypochlorite, requires a current density in the range of 750 to 950 mA/m2 with a sodium hypochlorite dose of 15 mL/L to aim the best corrosion resistance (0 to 3 pits). Also, It was established that cathodic current density applied affects significantly the corrosion resistance, isn’t the same with sodium hypochlorite dose as evidenced by the respective statistical analysis.